8(d+4)=4(d-8)+4d

Simple and best practice solution for 8(d+4)=4(d-8)+4d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(d+4)=4(d-8)+4d equation:


Simplifying
8(d + 4) = 4(d + -8) + 4d

Reorder the terms:
8(4 + d) = 4(d + -8) + 4d
(4 * 8 + d * 8) = 4(d + -8) + 4d
(32 + 8d) = 4(d + -8) + 4d

Reorder the terms:
32 + 8d = 4(-8 + d) + 4d
32 + 8d = (-8 * 4 + d * 4) + 4d
32 + 8d = (-32 + 4d) + 4d

Combine like terms: 4d + 4d = 8d
32 + 8d = -32 + 8d

Add '-8d' to each side of the equation.
32 + 8d + -8d = -32 + 8d + -8d

Combine like terms: 8d + -8d = 0
32 + 0 = -32 + 8d + -8d
32 = -32 + 8d + -8d

Combine like terms: 8d + -8d = 0
32 = -32 + 0
32 = -32

Solving
32 = -32

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8.2(s+4)=6.7x+5.3 | | 5(2q-1)=2(q+3) | | -7(-13a)=5(3-5a) | | 5y-3(y-2)+6= | | 6(y+4)-2=52 | | 16-2n-5+8n=85 | | x/5=3/2 | | x=3+3.32i | | 16=-1d+6 | | 2b=-34 | | 10+3(x-13)=5(1-x)+14 | | -6x+2=-9+5x | | 4m+=13-m | | 7n-6+n=2(4n+3) | | (6a+11)=2a+83 | | x^2+121=2x^2 | | 7d-3d+5d-5-6d=0 | | b-2+3b+64=4 | | -136=8(1+6b) | | 16=2(x-1)-4 | | 4(3x+5)=104 | | 7.50=0.8c+0.5c | | 11=-7p+13+8p | | 6x-50=10-x | | 2m+23=7m-2 | | 0.5c-7.50= | | x^2-3x+24=0 | | 17x^2-22x+6=0 | | -4x+-40-6=-3-6 | | 4+4b=4 | | 7n-18+1=19 | | 8.2(s+4)=6.7x+5.2 |

Equations solver categories